'In situ synthesis' of source material from elemental Si and C during SiCPVT growth process and characterization using digital X-ray imaging - Wellmann, Peter; Herro, Ziad Georges; Straubinger, Thomas; Winnacker, Albrecht (Materials Science Forum, 2002)
Silicon Carbide (SiC) single crystals grown by the physical vapor transport technique usually use SiC powder as source material which was synthesized in a previous technological step. We have investigated the possibility to combine the SiC synthesis and SiC crystal growth into one process. Using a SiC wafer on top of the source material which shields the SiC seed from the exothermal Si + C insitu synthesis we were able to grow SiC crystals with structural properties comparable to the conventional process; i.e. 40mm 6H-SiC single crystal diameter and micropipe density <200cm(-2
Keywords: In Situ Synthesis; Physical Vapor Transport Growth; Source Material; X-Ray Imaging